Reconstruction of Legal Norms Through Harmonization of Sexual Crime Laws - Febry Dwi Prehatiningsih; Edshafa Muharatulloh; Winda Rahmawati; Safira Wulandari; Tahegga Primananda Alfath (Unnes Law Journal, 2023)
Harmonization and synchronization are required in the development of laws and regulations in order to strengthen the law and avoid overlapping regulations. Sexual crime legislation, there is the phrase "without the consent of the victim" or better known as sexual consent in the Regulation of the Minister of Education and Culture of Research and Technology Number 30 of 2021 concerning the prevention and handling of violence in the higher education environment (Permendikbudristek 30/2021), the term of sexual consent is not in line with the sexual crime regulations in other laws and regulations. This research method uses a normative approach that refers to legislation and norms, as well as a conceptual approach to explain the theory used systematically. The results of the study indicate that sexual consent is inappropriate for sexual violence, because sexual consent is contrary to the Criminal Code, the Law on the Elimination of Domestic Violence, the Trafficking in Persons Act, the Pornography Law, and the Act Sexual Violence.